2012
DOI: 10.1007/s00167-012-1959-9
|View full text |Cite
|
Sign up to set email alerts
|

Scapular dyskinesis and SICK scapula syndrome following surgical treatment of type III acute acromioclavicular dislocations

Abstract: Retrospective study, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 18 publications
0
38
0
4
Order By: Relevance
“…Alguns estudos recentes demonstraram que o tratamento conservador das lesões grau III altera a cinemática da escápula. 9 No tratamento do atleta, consideraç ões individuais devem ser levadas em conta, como tipo de esporte, período do campeonato de ocorrência da lesão, nível de atividade, posição do jogador e tipo de arremesso. Na nossa opinião, um paciente não atleta com uma lesão do tipo III deve ser inicialmente conduzido de forma não cirúrgica, com foco em uma reabilitação adequada.…”
Section: Discussionunclassified
“…Alguns estudos recentes demonstraram que o tratamento conservador das lesões grau III altera a cinemática da escápula. 9 No tratamento do atleta, consideraç ões individuais devem ser levadas em conta, como tipo de esporte, período do campeonato de ocorrência da lesão, nível de atividade, posição do jogador e tipo de arremesso. Na nossa opinião, um paciente não atleta com uma lesão do tipo III deve ser inicialmente conduzido de forma não cirúrgica, com foco em uma reabilitação adequada.…”
Section: Discussionunclassified
“…In a similar study 7 on asymptomatic overhead athletes, it was found that conscious patient's control of the scapula orientation significantly increases the activation of the three parts of the trapezius without changing the UT/ MT and UT/LT ratios in two of the four exercises described by Cools et al 25 , namely the prone extension and sidelying external rotation of the arm. dyskinesis and one patient (2.9%) was affected by SICK syndrome 14 . Surgical treatment of Type III AC dislocation would, thus, be highly effective in preventing scapular dyskinesis and SICK syndrome.…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 99%
“…Scapular dyskinesis is not necessarily a pathologic term. In fact, it may be found either in asymptomatic subjects or in patients with pain in the shoulder girdle [3][4][5][6] , and, in both cases, in subjects playing no overhead sports or in athletes involved in several types of overhead sports, such as baseball, rugby, waterpolo, tennis, volleyball, swimming and badminton, as reported in the literature, 5,[7][8][9][10][11][12] and in patients with sequelae of clavicle fractures or AC joint injuries 13,14 . Burkhart et al 1 who recognised the importance of scapular dyskinesis in overhead athletes complaining of shoulder pain introduced the acronym SICK (Scapular malposition, Inferior medial border prominence, Coracoid pain and malposition and dysKynesis of scapular motion) to indicate the clinical findings that are present in the dyskinetic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2]. In III grade cases, medical opinions begin to diverge as conservative treatment may result in scapular dyskinesis, SICK scapula syndrome, which causes discomfort in the shoulder girdle, weakness, and inability to take part in sporting activities [3]. If there is any doubt as to whether a patient would definitely benefit from surgery, it is reasonable to treat the patient expectantly, and if he has persistent symptoms, then a later stabilization operation may be done [4].…”
Section: Introductionmentioning
confidence: 99%